Judging Banks' Risk by the Profits They Report - Meiselman, Ben S.,Nagel, Stefan,Purnanandam, Amiyatosh (National Bureau of Economic Research, 2023)
In competitive capital markets, risky debt claims that offer high yields in good times have high systematic risk exposure in bad times. We apply this idea to bank risk measurement. We find that banks with high accounting return on equity (ROE) prior to a crisis have higher systematic tail risk exposure during the crisis. Proximate causes of crises differ, but the predictive power of ROE is pervasive, including during the financial crisis of 2007-2010 and the recent crisis triggered by the collapse of Silicon Valley Bank. ROE predicts systematic tail risk much better than conventional measures based on risk-weighted assets
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Bankrisiko; Bank; Rentabilität; Kreditrisiko; Systemrisiko; Finanzmarkt; Finanzkrise; USA; return on equity; General